Enhancing Professional Development through International Collaborative Dialogue: A Study of Malaysian and Australian Pre-Service Teachers - Maniam, Vegneskumar; Gerard, Tay; Harrington, Ingrid; Tranchard, Hayley; Bennett, Susan (UUM Press, 2025)
Purpose - Despite the comprehensive nature of pre-service teacher training programs in Malaysia, the first year of teaching remains a challenging period for novice educators. Effective practices to support the transition to professional life is therefore crucial for teacher retention. This paper presents findings from a prospective study of an ongoing project model developed collaboratively by academics from an Australian public university and a Malaysian public teacher education provider. Together, they facilitated a series of international, dialogue-focused workshops designed to foster collaboration and conversation between Malaysian and Australian pre-service teachers. Methodology - Pre-service teachers from Australia and Malaysia identified key areas of concern within their respective educational systems. Through virtual classroom sessions, they collaboratively discussed these issues and shared strategies for addressing them. Employing a qualitative approach, the project conducted semi-structured interviews with 10 Malaysian pre-service teachers to explore their participation in the virtual dialogues. The interviews also examined the participants’ key takeaways, classroom teaching applications, and the challenges of engaging in online discussions. Findings - Analysis of the interview data revealed six key themes: (1) Games in the Classroom, (2) Inclusive Mindsets, (3) Planning in Teaching and Learning, (4) Computer-Mediated Communication (CMC), (5) International and Comparative Education, and (6) Workshop Sustainability Significance - This study highlights the potential of the online collaborative project model to enhance pre-service teachers’ international collaboration skills. It underscores the model’s value as a sustainable professional development tool and a supportive framework for easing the transition to professional teaching